Pengaruh Pemberian Terapi Sujok pada Pasien Nyeri Post General Anestesi - Cahaya Nugraheni; Ririn Zuhairini (Lembaga Pengembangan Kinerja Dosen, 2026)
Postoperative pain is one of the most common complaints experienced by patients following surgical procedures performed under general anesthesia. Inadequate pain management may delay the recovery process, increase patient discomfort, and contribute to various physiological complications. One complementary therapy with potential analgesic benefits is Sujok therapy, a reflex point stimulation technique applied to the hands and feet that is believed to activate the body's natural pain-relief mechanisms. This study aimed to analyze the effect of Sujok therapy on pain intensity among post-general anesthesia patients at PKU Muhammadiyah Bantul Hospital. A quasi-experimental two-group pretest–posttest design was employed involving 30 respondents, who were allocated into intervention and control groups. Pain intensity was assessed using the Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon Signed-Rank Test and the Mann–Whitney U Test. The results showed that the mean pain score in the intervention group decreased from 5.87 ± 1.19 to 2.93 ± 1.03 (p = 0.001), whereas the control group showed a reduction from 5.73 ± 1.03 to 4.93 ± 1.03 (p = 0.042). The Mann–Whitney U Test revealed a significant difference in pain reduction between the two groups (p = 0.000). These findings indicate that Sujok therapy is effective in reducing pain among post-general anesthesia patients and has the potential to serve as a safe, simple, and easily applicable complementary intervention in perioperative nursing practice.